Framing The Future: Exploring AI Narratives in Indonesian Online Media Using Topic Modelling - Octavianto, Adi Wibowo; Priyonggo, Ambang; Setianto, Yearry Panji (UI Scholars Hub, 2024)
Artificial Intelligence (AI) is a transformative force shaping society, and online media plays a pivotal role in shaping public perceptions of it. Given the media’s influence, understanding its framing of recent AI advancements, such as the emergence of Large Language Models (LLMs) like ChatGPT, becomes increasingly critical. These models have revolutionized human-machine interaction and are subject to media narratives that can significantly influence public understanding and policy. This research explores the framing of AI narratives in Indonesian online media through the utilization of topic modelling. The study aims to uncover the dominant narratives and themes surrounding AI, including the nuanced portrayal of LLMs and Chat GPT. Using a dataset of online articles and news pieces on AI in the Indonesian context, topic modelling analysis identifies and analyzes the key topics and sentiments. The findings reveal that Indonesian online media tends to portray AI positively, emphasizing its potential for innovation and economic growth. However, concern about ethical implications and job displacement are also present. These findings provide important insights for AI developers, journalists, and policymakers, highlighting the importance of balanced reporting to shape informed public opinion and ethical AI practices.